2020
DOI: 10.1148/ryai.2020190102
|View full text |Cite
|
Sign up to set email alerts
|

Fully Automatic Volume Measurement of the Spleen at CT Using Deep Learning

Abstract: To develop a fully automated algorithm for spleen segmentation and to assess the performance of this algorithm in a large dataset. Materials and Methods:In this retrospective study, a three-dimensional deep learning network was developed to segment the spleen on thorax-abdomen CT scans. Scans were extracted from patients undergoing oncologic treatment from 2014 to 2017. A total of 1100 scans from 1100 patients were used in this study, and 400 were selected for development of the algorithm. For testing, a datas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 37 publications
(45 reference statements)
1
20
0
Order By: Relevance
“…In comparison, measuring the axial plane diameter is easy to implement in clinical routines. Nevertheless, the first results from a fully automated spleen segmentation with the use of artificial intelligence methods have shown promising results and it is likely that those tools will become increasingly available in the daily clinical routine 32,33 . These novel methods offer an automated report of the splenic volume, ad hoc after imaging, which will tremendously reduce the time investment.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison, measuring the axial plane diameter is easy to implement in clinical routines. Nevertheless, the first results from a fully automated spleen segmentation with the use of artificial intelligence methods have shown promising results and it is likely that those tools will become increasingly available in the daily clinical routine 32,33 . These novel methods offer an automated report of the splenic volume, ad hoc after imaging, which will tremendously reduce the time investment.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, the spleen is a parenchymatous organ surrounded by peri-splenic fat and therefore easy to automatically segment. Humpire-Mamani et al have shown that a neural network can be trained to segment the spleen in CT scans with an accuracy that is comparable to an experienced radiologist [34,35]. Such a performance would not be expected for involved lymph node sites, which can occur on any site within the scan volume.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, a U-Net for automatic spleen segmentation was successfully trained with high accuracy. The U-Net is currently the state of the art for automatic image segmentation and was also used by Humpire-Mamani et al for spleen segmentation [34]. When a U-Net is trained on scans from different scanners, with different slice thicknesses and so on, it learns a general concept of the appearance of a spleen that is independent of the actual imaging settings.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, from a recently presented review work, liver segmentation can reach accuracy of 95% in terms of Dice coefficients [36]. In a recent work for spleen segmentation [65], 96.2% Dice score is reported. However, it is worth re-thinking that is abdominal organ segmentation a solved problem?…”
Section: Limitations Of Existing Abdominal Organ Segmentation Methods and Benchmark Datasetsmentioning
confidence: 99%